The athlete's perception of coaches` behavior towards competitors with a different sports level - Siekanska, M.; Blecharz, J.; Wojtowicz, A.- (Journal of Human Kinetics, 2013)
The study was designed to examine how active and former athletes across a different sports level perceived coaching behavior. Eighty competitive athletes (44 males and 36 females; 21.89 ±1.48 years of age; 8.35 ± 3.65 years of competitive experience) from the University School of Physical Education in Cracow, Poland, participated in the study. They represented both individual (n = 50) and team sports (n = 30). Seventeen participants were internationally renowned and 63 were recognized for competitive excellence at a national level. The participants responded to a demographic survey and the Coaches` Behaviors Survey. The qualitative analysis procedures were employed to extract themes from open-ended questions. It was confirmed that coaches who perceived their athletes as more skilled, also treated them differently. Female athletes as compared with male athletes, more frequently pointed at the leniency in coach`s behavior towards highly skilled athletes, and perceived it as a factor inhibiting athletic development. Additionally, women often found individualization of the training process as a behavior reinforcing development. Less accomplished athletes more often pointed out to "a post-training session interest in the athlete" as directed only towards more accomplished counterparts; however, they indicated "leniency and favoring" less often than the athletes with international achievements. They also listed "excessive criticism" as a type of behavior hindering development, but they indicated coaches` "authoritarianism and distance" less frequently than the more accomplished counterparts. The study added data to the discussion of the Pygmalion effect and the phenomenon of the self-fulfilling prophecy both in general (Rosenthal and Jacobson, 1968; Harris and Rosenthal, 1985; Jussim, 1989) and sport psychology (Harris and Rosenthal, 1985; Horn et al., 1998; Solomon and Kosmitzki, 1996; Solomon et al., 1998; Solomon, 2001).